Implementasi Metode Waterfall Untuk Sistem Persediaan Aksesoris Sandal Pada Toko Accessories H Engkos - Ridwan, Muhammad; Suryani, Indah; Gunawan, A; Nurwahyuni, Siti (JAIS - Journal of Accounting Information System, 2021)
Toko Accesories H. Engkos is a business that is engaged in the sale of shoe sandal accessories. In carrying out this business, H.engkos always encounters financial recording problems. He was always confused about how much income came in and went out on the way just starting out, plus the manually written notes. The author finally decided to conduct research with Data Collection Methods starting from the Literature Study, followed by Observation, and ended with Interviews as a working method for collecting data and software development methods that will be applied to research at the Toko Accesories H. Engkos, namely by using the method Waterfall or Sequential classic lifeline where the waterfall model is often also called a linear sequence model or classic lifeline. System development is carried out sequentially starting from the analysis, design, coding, testing and support stages. Toko Accesories H. Engkos requires the presence of a system in making financial reports, so that it can be faster to see the financial condition of the business being run and increase confidence in making decisions because the reports are getting better. With this sales and inventory information system, it is hoped that the goods management process will be more effective and efficient.